STUDI ETNOBOTANI TUMBUHAN PANGAN YANG TIDAK DIBUDIDAYAKAN OLEH MASYARAKAT LOKAL DI DESA LUBUK BUMBUN KECAMATAN MARGO TABIR KABUPATEN MERANGIN - Ali Imran; Rivo Yulse Viza; Pitri Handayani (BIOCOLONY, 2020)
This research is motivated by the absence of more detailed and published research data regarding food plants that are not cultivated by local people in Lubuk Bumbun Village, Margo Tabir District, Merangin Regency. For this reason, this research was conducted with the aim of knowing public knowledge and describing the types of food plants that were not cultivated, studying the types of non-cultivated food plants that would be utilized, and knowing how to process non-cultivated food plants. The research was conducted using descriptive methods with data collection techniques through in-depth interviews with various sources, field observations, documentation and literature study. The selection of respondents was done by using snowball sampling. Based on the research that has been carried out, it was obtained 36 species from 22 families of food plants that were not cultivated by the people of Lubuk Bumbun village. Of the 22 families, there are 2 families with many species, namely the Moraceae and Fabaceae families. The dominant part of non-cultivated food plants used was fruit (26 species). The dominant method of processing food plants that are not cultivated is to eat them directly (19).